Study of Materials Retrieved from a Ketzin CO2 Monitoring Well. (July 2017) - Gawel, Kamila; Todorovic, Jelena; Liebscher, Axel; Wiese, Bernd; Opedal, Nils
Abstract: The Ketzin pilot site is the longest operating onshore CO2 storage site in Europe. CO2 injection began in June 2008 and ended in August 2013. In total five wells were drilled at the Ketzin pilot site. The Ketzin monitoring well 202 has been abandoned in autumn 2015. During the abandonment, well construction material samples were retrieved. The samples were retrieved from the cementitious plug as well as from the steel casing and the production string at different depths. The samples were analyzed by a set of complementary experimental techniques. The structure and macroporosity of cement samples were studied using X-ray computed tomography (CT) and scanning electron microscopy (SEM). The structural changes associated with hardening of the cementitious material downhole compared to the reference topside sample have been described. Casing and production string samples were studied using light optical microscopy to investigate microstructural changes resulting from CO2 exposure. The relation between corrosion degree and the depth from which the samples were retrieved has been established.